KEWAJIBAN DAKWAH DALAM AL-QUR’AN ANTARA FARDU AIN DAN FARDU KIFAYAH (STUDI KOMPARATIF ATAS TAFSIR IBN KATSÎR DAN TAFSIR AL-MISHBÂH) - Habibullah, Kabir Al Fadly; Nawawi, Abd. Muid; Zuhri, Saifuddin (Universitas Islam Syekh-Yusuf, 2022)
Today, at a time when the general problem is increasingly complex and the need for religious references is escalation, there is a spirit to answer this with the da'wah movement both individual and collective. This condition according to the researchers is very good, but there is often a fundamental understanding bias about who is actually entitled and obliged to deliver Da'wah and how the law actually discriminates against the perspective of the Qur'an. Based on this problem, researchers are interested in exploring how ibn Katsir and M. Quraish Shihab's interpretation of the obligation of Da'wah and the implications of the socio-historical background of both interpretations in comparative analysis. The approach used in this study is qualitative with comparative study methods. Data collection techniques in the form of library studies and observations are analyzed in the form of descriptive analysis techniques with analytical-comparative methods. The theory used to strengthen as a research scalpel is the theory of genetic structuralism of Lucien Goldmann who explains that work or text is the work of the author, in this case, Mufasir as the author of the text as well as the fact of history that conditioning the emergence of such a work or text.